(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
At a broader theoretical level, the subject matter of this article is theater as a sui generis artistic medium of testimony and memory of the Shoah (according to scholars like Robert Skloot and Grzegorz Niziołek, among others). This issue is addressed in the background of Polish theater and drama from the immediate post-war period to the present day – an impressively rich body of creative achievements in its most part still unknown in Brazil. For the purpose of exemplifying and examining particular aspects of the problem, two major plays still untranslated into Portuguese – Pieszo (On ​​foot; 1980), by Sławomir Mrożek, and Pułapka (The trap; 1982), by Tadeusz Różewicz – are analyzed and discussed in more detail.